Audit committee attributes and cosmetic accounting in Nigeria: The moderating effect of audit price. Issue 2 (1st November 2019) - Bala, Hussaini; Amran, Noor Afza; Shaari, Hasnah
Abstract : Purpose: The literature on the influence of audit committees (ACs) and cosmetic accounting (CSA) is scarce. This paper aims to examine the influence of AC attributes on CSA and how this relationship is moderated by the audit price (AUPR). Design/methodology/approach: The study used pooled logistic regressions to analyse 624 firm-year observations of listed companies in Nigeria from 2008 to 2016. Findings: The results show that AC financial accounting expertise, AC legal expertise and female AC membership were negatively related to CSA. The negative relationship is highly pronounced when a firm incurs higher audit fees. Results for the robustness checks were similar, even with changes to the measurements of dependent and independent variables and alternative estimation. Practical implications: This study can benefit policymakers and regulators, enabling them to better appreciate the importance of AC attributes and AUPR in curtailing artificial manipulation and enhancing financial reporting quality. Social implications: This study can benefit policymakers and regulators, enabling them to better appreciate the importance of AC attributes and AUPR in curtailing artificial manipulation and enhancing financial reporting quality. Originality/value: The findings provide an initial insight into the moderating effect of AUPR on the relationship between AC attributes and CSA.